PROFITABILITAS SEBELUM DAN SESUDAH PENGALIHAN DANA HAJI DARI BANK KONVENSIONAL KE BANK SYARIAH (Studi Kasus di Bank Syariah Mandiri Periode 2011-2016) - Arini, Tsani I smatu (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan dan Akuntansi, 2018)
The aim of this study was to find out the profitability of Bank Syariah Mandiri before and after the transfer of Hajj Fund from conventional banks to Islamic banks in 2014. Some of the hajj fund that transferred to Islamic banks was placed in Bank Syariah Mandiri. The Data that used in this study is Return On Assets (ROA) ratio which stated in Quarterly Financial Report of Bank Syariah Mandiri,10 quarters of ROA before the transfer of hajj fund that started from the third quarter of 2011 until the last quarter of 2013, and 10 quarters of period ROA after the transfer of hajj fund that started from the third quarter of 2014 until the last quarter of2016. The model that used by this study iscomparison testwith paired-t test. The result of this study shows us that there was a difference in profitability of Bank Syariah Mandiri before and after the transfer of hajj fund from conventional banks to Islamic banks.Â Keywords: Return On Aset (ROA), Profitability, Islamic Bank, Hajj Fund, Fund Transfer